Community Service and Green Economy-Based MSME Strengthening in Supporting Sustainable Poverty Alleviation - Lilik Nurcholidah; Ratna Handayati; Moh. Muklis Sulaeman (PT. LITERASI SAINS NUSANTARA, 2026)
This study aims to enrich the literature on community service in the context of strengthening Micro, Small, and Medium Enterprises (MSMEs) based on the green economy to support sustainable poverty alleviation. The research employs a qualitative approach using a literature review method, analyzed descriptively. Data were obtained from Google Scholar and various credible websites with a publication range from 1991 to 2026. Out of 50 articles identified in the initial stage, a rigorous selection process was conducted based on relevance, quality, and methodological suitability, resulting in 36 articles for further analysis. The findings indicate that community service plays a strategic role in enhancing MSME capacity through knowledge transfer, mentoring, and participatory empowerment. The integration of green economy principles, such as resource efficiency, waste management, and renewable energy utilization, has proven to improve operational efficiency, product value, and MSME competitiveness. Furthermore, this approach contributes to improving community welfare and reducing poverty in a sustainable manner. However, its implementation still faces various challenges, including limited environmental literacy, technological access, and policy support. Therefore, synergy among government, academia, and the private sector is required to develop integrated and sustainable community service programs.